Queen Clarion's Secret - Morris, Kimberly; Illustrated by Shimabukuro, Denise ; Brown, Adrienne and Pickens, Charles (New York Random House)
Fairies Beck, Prilla, and Lily investigate the disappearance of Queen Clarion, the ruler of Pixie Hollow
Include Color Illustration
Keywords: Fairies -- Adventure stories -- Kings and rulers